2010
DOI: 10.4049/jimmunol.1001718
|View full text |Cite|
|
Sign up to set email alerts
|

Th17 Cells Contribute to Viral Replication in Coxsackievirus B3-Induced Acute Viral Myocarditis

Abstract: Acute viral myocarditis (AVMC) is characterized by virus-triggered myocardial inflammation, and Coxsackievirus B3 (CVB3) is the primary pathogen. We previously proved that Th17 cells, besides having proinflammatory effects, were involved in AVMC by enhancing humoral response. However, the relationship between Th17 cells and CVB3 replication remains unknown. In this experiment, we infected BALB/c mice with CVB3 for establishing AVMC models and then found that, with the increase of viral replication, the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 24 publications
2
90
0
3
Order By: Relevance
“…Interleukin (IL)-17-expressing T cells (termed Th17) and forkhead box protein 3 (FoxP3 + ) regulatory T cells (Treg) are newly identified subsets of CD4 + Th cells, and developing studies have reported that both of them have a pathogenic role in AD [3][4][5]. More recently, a novel independent Th-cell subset, characterized by expression of high amounts of IL-9, which do not express T-bet, GATA-3, retinoic acidrelated orphan receptor gamma T (RORγt) or FoxP3, subset-determining transcription factors associated with Th1, Th2, Th17 and Treg cells, had been recognized as 'Th9' cells [6][7][8][9]. Although the mechanism for the differentiation and proliferation of Th9 cells has not been elucidated fully, the transcription factor PU.1 is required for the differentiation and functional activation of Th9 cells; indeed, PU.1 binds directly to the IL-9 promoter to trigger specific chromatin modifications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin (IL)-17-expressing T cells (termed Th17) and forkhead box protein 3 (FoxP3 + ) regulatory T cells (Treg) are newly identified subsets of CD4 + Th cells, and developing studies have reported that both of them have a pathogenic role in AD [3][4][5]. More recently, a novel independent Th-cell subset, characterized by expression of high amounts of IL-9, which do not express T-bet, GATA-3, retinoic acidrelated orphan receptor gamma T (RORγt) or FoxP3, subset-determining transcription factors associated with Th1, Th2, Th17 and Treg cells, had been recognized as 'Th9' cells [6][7][8][9]. Although the mechanism for the differentiation and proliferation of Th9 cells has not been elucidated fully, the transcription factor PU.1 is required for the differentiation and functional activation of Th9 cells; indeed, PU.1 binds directly to the IL-9 promoter to trigger specific chromatin modifications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that in VMC mice, myocardial histological changes are similar to anthropology lymphocytic myocarditis (Yuan et al, 2010b), and thus this model has been widely used for studying both the acute infectious phase and the chronic immune phase of human VMC. Both the direct viral response and immune-mediated mechanisms have been shown to contribute to the pathogenesis of acute injury and subsequent cardiac remodeling (McManus et al, 1993;Cooper, 2003).…”
Section: Etiology and Pathogenesis Of Autoimmune Myocarditismentioning
confidence: 99%
“…Cardiac pathology was improved after IL-17 neutralization and correlated with reduced viral replication and decreases in cardiac inflammatory cytokines IL-17, TNF-, and IL-1 . This study implicates Th17 cells in contributing coxsackeivirus B3 replication in viral myocarditis, and implicates IL-17 as a target for regulating antiviral immune responses (Yuan et al 2010). Th17 cells are activated by IL-23, a cytokine likely produced by activated macrophages and dendritic cells, through receptor interactions made of IL-12R 1 and IL-23 receptor (Langrish et al 2005).…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%